How to play in slow time: Embodying creativity literacies in digital learning environments. (February 2023) - Trezise, Bryoni; Tálamo, Alexandra; White, Maria
This article considers how the emergent digital pedagogies used in a new creativity course run at the Univeristy of New South Wales contribute to the building of sensed, intuitive and embodied creativity literacies. In doing so, it addresses questions around the function of tertiary education within an accelerated, digitised and COVID-19-saturated globe. For while creativity is being touted as what every student needs – and what every employer wants – there is little understanding of how this most mystifying of skills can be taught to students in broad disciplines. There is even less understanding of how full-bodied modalities of creative cognition can be leveraged as moments of deep insight in the socially distanced realm of the digital. Drawing on hands-on methods from ground-breaking musicians, performers, dancers and writers, this article shows how the neuroscience and psychology of taking 'beautiful risks', committing to uncertainty and paying attention can be harnessed in digital learning. These dynamic digital pedagogies are principled in embodied liveness, playful interactivity and generative curiosity. They support students with practical strategies to take risks with imagination, discover through collaboration and work responsively in relation to diverse situations.